2019
DOI: 10.1080/03080188.2019.1603873
|View full text |Cite
|
Sign up to set email alerts
|

Measuring gender in R&I – theories, methods, and experience

Abstract: This article provides an overview of the theoretical assumptions, methods, and key results from the Evaluation Framework for Promoting Gender Equality in Research and Innovation (EFFORTI) project, which was funded by the European Commission. The purpose of EFFORTI was to analyse the impact of interventions to promote gender equality in research and innovation (R&I), and to establish criteria for more responsible and responsive research and innovation (RRI) systems in Europe. This article provides an overview o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…A review of gender equity initiatives within research‐ and innovation‐focused organisations in Europe found the most successful initiatives were those which took local contextual factors into account; however, the same review also found highly variable intensity and quality of evaluation to measure such success (Palmén et al. 2019). Kalev, Dobbin and Kelly (2006) asked whether we were using “best practice” or “best guesses” in developing gender equity programmes, noting “whereas there has been a great deal of research on the sources of inequality, there has been little on the efficacy of different programs for countering it…We know a lot about the disease…but not much about the cure” (p. 590).…”
Section: Identifying Evidence Of Influence In Gender Equity Programmesmentioning
confidence: 99%
“…A review of gender equity initiatives within research‐ and innovation‐focused organisations in Europe found the most successful initiatives were those which took local contextual factors into account; however, the same review also found highly variable intensity and quality of evaluation to measure such success (Palmén et al. 2019). Kalev, Dobbin and Kelly (2006) asked whether we were using “best practice” or “best guesses” in developing gender equity programmes, noting “whereas there has been a great deal of research on the sources of inequality, there has been little on the efficacy of different programs for countering it…We know a lot about the disease…but not much about the cure” (p. 590).…”
Section: Identifying Evidence Of Influence In Gender Equity Programmesmentioning
confidence: 99%
“…The study of the gender issue, like the other key areas of RRI on the EU agenda (ethics, governance, public engagement, scientific education and open access), predates the formulation of this approach to research and innovation by the European Commission in 2010. While the literature on gender equality in R&I is abundant, with a history dating back at least to the 1990s [24], and while it continues to grow [25], the same is not true of its relationship with RRI either in the theoretical field of its conceptualization [26], or in the practice of RRI [27], or in the existing perceptions of RRI [28].…”
Section: Gender Mainstreaming and Randimentioning
confidence: 99%
“…The imbalance is particularly clear in STEM areas of knowledge [35]. • The question of whether there are work-life balance policies or specific programs to improve the women's skills for promotion at work can also be an obstacle [24]. • the introduction of the gender perspective into actions or funding to produce a structural change [36].…”
Section: Gender Mainstreaming and Randimentioning
confidence: 99%
“…The knowledge base generated by the evaluation can be used to develop targeted policies. Noteworthy, the evaluation of the policy program to be established should already be considered during its development (Palmén et al, 2019). Key questions are which indicators can be used to determine whether a program has been successful or whether adjustments are necessary.…”
Section: Recommendations For Designing a Discrimination Reduction Pro...mentioning
confidence: 99%
“…Measures. An anti-discrimination program should generally be implemented through context-specific interventions (Palmén et al, 2019). This means that the program should be tailored as appropriately as possible for the specific situation and challenges in an organization.…”
Section: Policy Implementation: Embedding Objectives Through Context-...mentioning
confidence: 99%